An advanced case of pediatric ciliary body medulloepithelioma with detailed literature review - Alsulaiman, Hamad M.; AlThaqib, Rawan; Maktabi, Azza M.Y.; Alkatan, Hind M.; Elkhamary, Sahar M.; Schellini, Silvana Artioli [UNESP] (Wolters Kluwer, 2024)
Introduction and importance: Medulloepithelioma is the second most common primary intraocular malignant tumor in children but is often diagnosed late, which worsens the prognosis. Case presentation: We are reporting a 6-year-old boy presenting with a ciliary body (CB) teratoid malignant medulloepithelioma (TMM), which was missed at the initial presentation. We added our case to the 97 previously reported cases in our literature review that were confirmed by cytological or histopathological examination. Discussion: Medulloepithelioma has a wide age range at presentation with a mean of 5.3 ± 4.1 years, and slight male predominance (M: F ratio of 1.15). Clinically, the main symptoms/ signs are reduced visual acuity, lens changes, or a pupil “mass.” Almost all reported medulloepitheliomas were unilateral (98 %). Histopathologically, non-teratoid malignant medulloepithelioma (NTMM) (35.7 %) and TMM (34.5 %) were the commonest. Enucleation was the main treatment modality because of the large tumor size of 72.7 %. A combination of chemotherapy and/or radiotherapy was used in 15.1 % and brachytherapy for small lesions in 14.1 %. Orbital exenteration was needed in 3 cases because of orbital invasion. Conclusion: A CB medulloepithelioma tumor can be easily missed, diagnosed late, with less chance for globe salvaging. The malignant types are more common and may result in orbital invasion, requiring even more extensive surgery. Therefore, when facing a child with lens changes, a pupil “mass,” or raised intraocular pressure, pediatricians and general ophthalmologists must have an earlier suspicion and be aware of this rare entity to improve outcomes and reduce loss of vision or other disease-related morbidity.
Keywords: Glaucoma; Intra-ocular tumor; Medulloepithelioma; Pediatric; Teratoid, malignant